76.3k views
5 votes
Which is the simplified form of the expression

Which is the simplified form of the expression-example-1
User Jay Modi
by
5.0k points

2 Answers

5 votes

Answer:

hes right^

Explanation:

User Duncan Edwards
by
5.2k points
3 votes

((6^(-4))^(-9))/(6^6)=(6^((-4)(-9)))/(6^6)=(6^(36))/(6^6)=6^(36-6)=6^(30)\\\\\text{Used:}\\\\(a^n)^m=a^(n\cdot m)\\\\(a^n)/(a^m)=a^(n-m)
User Marcelo Santos
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.